Perlindungan Konsumen dalam Transaksi Bisnis Online antara Kebebasan Berkontrak dan Kewajiban Pelaku Usaha : Kajian Yuridis Normatif - Sulasno; Queencyla Rifani Putri; Inarotul Fikria (JUSTNESS - Jurnal Hukun dan Agama, 2026)
The rapid growth of online business transactions in Indonesia has been accompanied by an increase in consumer protection violations. This study aims to examine consumer protection in online business transactions, particularly concerning the balance between business actors' freedom of contract and their obligations to provide information and ensure transparency. This research employs a qualitative method with a normative juridical approach, utilizing secondary data. The findings reveal a disparity between existing regulations and actual practices in the field, highlighting several obstacles in law enforcement and proposing innovative solutions to enhance consumer protection without hindering the growth of online businesses. In conclusion, regulatory harmonization, increased legal awareness, and the use of technology are essential to achieving an optimal balance between consumer protection and ease of doing business. Keywords: Consumer Protection; Online Transactions; Business Law.